Effects of Digital Marketing and Service Quality Towards Business Performance That Is Mediated by Competitiveness - Hadiyati, Ernani (British Journal of Marketing Studies, 2023)
The research aimed to analyze effects of digital marketing and service quality towards business performance with competitiveness as a mediating variable. The research sample involved 114 people of meatball-culinary micro entrepreneurs in Malang City, East Java Province, Indonesia. The sampling technique applied purposive sampling. Research data analysis was done with some steps including frequency distribution, validity and reliability tests, path analysis method with SPSS software and for mediation test with sobel test. The research results showed: first, that digital marketing had significant effect on business performance with the mediation of competitiveness and the partial mediation model. Second, service quality had a significant effect on business performance with the mediation of competitiveness and the full mediation model. Results of the Sobel test proved that competitiveness was the right mediating variable for digital marketing and service quality influenced business performance. The research results practically contributed ideas to meatball-culinary micro-entrepreneurs in implementing digital marketing, service quality, competitiveness and business performance.